Characterization of key aroma compounds in low-salt fermented sour fish by gas chromatography-mass spectrometry, odor activity values, aroma recombination and omission experiments. (15th December 2022) - Zhang, Xiaojing; Gao, Pei; Xia, Wenshui; Jiang, Qixing; Liu, Shaoquan; Xu, Yanshun
Highlights: The aroma-profiles of fermented sour fish were characterized. Eighteen aroma compounds (OAV>1) were confirmed. Key aroma compounds were identified by recombination and omission experiments. Key aroma compounds included four esters, two aldehydes and one furan. Abstract: In this study, key aroma compounds of low-salt fermented sour fish were characterized using headspace solid-phase micro extraction (HS-SPME) coupled with gas chromatography-mass spectrometry (GC–MS), odor activity values (OAV) and aroma recombination and omission experiments. Eighty-eight volatile compounds, including esters, aldehydes, alcohols, acids, furans and pyrazines, were identified by HS-SPME-GC–MS. Eighteen aroma-active compounds were quantified by employing calculation of OAV greater than 1. A recombination aroma model prepared using aroma-active compounds based on the odorless fish matrix sensorially matched the aroma of fermented sour fish with a score of 4.5 out of 5. The omission experiment showed that 7 out of 18 compounds had a significant contribution to the overall aroma ( P < 0.05). The key aroma compounds of fermented sour fish were concluded to be ethyl acetate (OAV = 189), ethyl hexanoate (OAV = 66), isoamyl acetate (OAV = 424), ethyl butyrate (OAV = 26), hexanal (OAV = 49), 1-hexadecanal (OAV = 14) and 2-pentylfuran (OAV = 13).